Prevalence and Clinical Characteristics of Headaches in PHACE Syndrome - Yu, JiaDe (J Child Neurol, 2015)
PHACE syndrome is a neurocutaneous disorder often involving the cerebral vasculature. PHACE patients appear to have early-onset and severe headaches more commonly than children without PHACE. The objective of this study was to characterize the clinical features and prevalence of headache by conducting a cross-sectional survey of families in two large PHACE registries. Sixty-six percent of eligible families completed the survey in which 62.7% of respondents reported headaches. Average age of headache onset was 48.8 months. Females were more likely to have headaches (68.6% versus 30.8%, p=.014). Families reported associated migrainous features including nausea (62.5%), vomiting (37.5%), photophobia (75%), and phonophobia (75%). Headaches occurred at least weekly in 29.4%, lasted ≥1 hour in 85.4%, and led to ≥1 hospital admission in 15.7%. Three respondents with headaches had at least one ischemic stroke. We demonstrated that headaches are common among PHACE patients, develop at an early age, and have migrainous features.